Antimicrobial Properties and Assessment of the Content of Bioactive Compounds Lavandula angustifolia Mill. Cultivated in Southern Poland - Izabela Betlej; Bogusław Andres; Tomasz Cebulak; Ireneusz Kapusta; Maciej Balawejder; Sławomir Jaworski; Agata Lange; Marta Kutwin; Elżbieta Pisulewska; Agnieszka Kidacka; Barbara Krochmal-Marczak; Piotr Borysiuk (Molecules, 2023)
Lavender is a valued plant due to its cosmetic, perfumery, culinary, and health benefits. A wide range of applications is related to the composition of bioactive compounds, the quantity and quality of which is determined by various internal and external factors, i.e., variety, morphological part of the plant, and climatic and soil conditions during vegetation. In the presented work, the characterization of antimicrobial properties as well as the qualitative and quantitative assessment of bioactive compounds in the form of polyphenols in ethanol extracts from leaves and flowers of Lavandula angustifolia Mill. intended for border hedges, cultivated in the region of southern Poland, were determined. The composition of the fraction of volatile substances and antioxidant properties were also assessed. The conducted research shows that extracts from leaves and flowers significantly affected the viability of bacterial cells and the development of mold fungi. A clear decrease in the viability of bacteria and C. albicans cells was shown in the concentration of 0.32% of extracts. Leaf extracts were characterized by a much higher content of polyphenols and antioxidant properties than flower extracts. The composition of volatiles measured by GC-MS was significantly different between the extracts. Linalyl acetate and ocimene isomers mix dominated in flower extracts, whereas coumarin, γ-cadinene, and 7-methoxycoumarin were identified as dominant in leaf extracts.